PERLINDUNGAN KONSUMEN DALAM PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Fahmi Prasetya, Agus; Rudy, I Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015)
Act number. 8 of 1999 on the Consumers Protection has a provision that States that all of the existing legislation and relates to consumer protection continue to apply, as long as it does not conflict or have been regulated by special laws. This paper aims to acknowledge and identify about arrangements on the protection of consumers in Indonesia. Types of research methods used in this research, is a kind of normative, legal research in the writing of this researching the sources of consumer law. So Indonesia in various laws and regulations have clearly and firmly set on the protection of consumers.
Keywords: Acts, Consumer Protection